COVID-19-related stress and anxiety are associated with negative body image in adults from the United Kingdom. (15th February 2021) - Swami, Viren; Horne, George; Furnham, Adrian
Abstract: The stress and anxiety caused by the coronavirus (COVID-19) pandemic presents a serious threat to psychological well-being in populations worldwide and may also extend to body image outcomes. To test this hypothesis, we conducted a preliminary study in which an online sample of adults from the United Kingdom ( N = 506, age M = 34.25 years) were asked to complete measures of perceived stress, stressful life events, trait anxiety, COVID-19-related stress and anxiety, and negative body image (body dissatisfaction and drive for thinness in women, body fat and muscularity dissatisfaction in men). The results of hierarchical regressions indicated that COVID-19-related stress and anxiety explained significant incremental variance in body image outcomes (Adj. Δ R 2 = .02 to .10), over-and-above demographics (age and body mass index) and perceived stress, trait anxiety, and stressful life events. These findings suggest that COVID-19-related stress and anxiety may shape body image outcomes under conditions of physical and social distancing. Highlights: COVID-19-related stress and anxiety associated with negative body image Effects similar across women and men using gender-specific body image outcomes Effects significant after variance accounted for by perceived stress, stressful life events, and trait anxiety